2020
DOI: 10.1111/ajt.15976
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus serologic matching in deceased donor kidney allocation optimizes high- and low-risk (D+R− and D−R−) profiles and does not adversely affect transplant rates

Abstract: is a major cause of morbidity and an occasional cause of mortality among kidney transplant recipients. Clinical consequences of CMV in immunosuppressed patients range from asymptomatic viremia to tissue invasive disease. Additionally, CMV has been associated with increased rates of bacterial and fungal infections, posttransplant lymphoproliferative disorder, rejection, allograft dysfunction and failure, cardiovascular complications, and new onset diabetes after transplant. 1,2 Despite significant improvements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 29 publications
1
27
0
1
Order By: Relevance
“…The combination of donor and recipient CMV status is already taken into account for kidney transplant allocation in some regions. Recently, Lockridge et al reported the outcomes following the implementation of a CMV‐matching policy for deceased donor allocation in Oregon and demonstrated a significant decrease in CMV viremia incidence 18 . In case of living donor transplant, a CMV negative donor could be preferred to a CMV positive one in the case of multiple donors if the recipient is seronegative, or in the event of a single donor participation in paired‐exchange program to allow allocation of a CMV negative donor could be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of donor and recipient CMV status is already taken into account for kidney transplant allocation in some regions. Recently, Lockridge et al reported the outcomes following the implementation of a CMV‐matching policy for deceased donor allocation in Oregon and demonstrated a significant decrease in CMV viremia incidence 18 . In case of living donor transplant, a CMV negative donor could be preferred to a CMV positive one in the case of multiple donors if the recipient is seronegative, or in the event of a single donor participation in paired‐exchange program to allow allocation of a CMV negative donor could be considered.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate the lingering CMV risk of the D+R– population and enhance the number of low-risk D–R– recipients, the 3 kidney transplant centers in the greater Oregon Donation Service Area (Oregon Health and Sciences University, Portland Veterans Administration, and Legacy Good Samaritan) implemented a novel CMV prevention strategy via matching deceased kidney donors and recipients by CMV serostatus. 16 In this pilot, kidneys from seropositive deceased donors were preferentially allocated to seropositive recipients, while organs from seronegative donors were allocated to seronegative recipients. Exceptions were made for patients with difficult-to-match high-panel reactive antibody (PRA) and medical urgency.…”
Section: Introductionmentioning
confidence: 99%
“…The methods of the CMV matching policy have been previously described and did not adversely affect transplant rates for identified at risk populations. 16 Also, CMV infection rates, cumulative duration of antiviral prophylaxis, and costs associated with antiviral prophylaxis and treatment improved dramatically after the policy change. 16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been considered a risk factor for allograft dysfunction and rejection. 1,2 HCMV infection or disease occurs according to the type of transplanted organ, immunosuppressive strategy, and host immune status. 3 Without preventive strategies, 40%-80% of transplant patients will develop HCMV infection.…”
Section: Introductionmentioning
confidence: 99%